ANALISIS STRATEGI PEMASARAN PEMPEK OMO KOTA BANDUNG - Junianto, Junianto -; Affandy, Faried; Firdaus, Nur Aini Azhar; Anggreini, Diah Ayu; Putri, Zaky Yoana (Politeknik Kelautan dan Perikanan Pangandaran, 2024)
Pempek OMO is an MSME that produces Palembang speciality food, pempek. In the same area, of course, there are competitors with the same product. To maintain production, Pempek OMO must have a strategy so that it can continue to compete. Therefore, it is necessary to analyze the marketing strategy of Pempek OMO. This research is categorized as qualitative research using primary and secondary data. Primary data is obtained through surveys to the place and interviews with the owner of Pempek Omo, while secondary data is obtained through literature available on the internet. Then SWOT analysis was conducted, internal factors and external factors of pempek OMO production. The result of the research is that the value-added ratio obtained is greater than 40%, which means that the business or production process of Pempek Omo has a high added value.